1981
DOI: 10.1001/jama.1981.03310410031022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Pyuria by Leukocyte Esterase Activity

Abstract: To evaluate whether leukocyte esterase activity is a useful biochemical marker of pyuria, we examined urine from 20 healthy volunteers, 47

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…The comparison of results between the dipstick and sediment analysis of WBCs done by the senior technolo- The results of the above study confirm the previously reported findings of the acceptable accuracy of the stick test in the detection of urinary leukocytes [1][2][3]. In addi tion, we also found that technologist bias is lesser when presence of WBCs is evaluated by the dipstick method as compared to sediment analysis.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The comparison of results between the dipstick and sediment analysis of WBCs done by the senior technolo- The results of the above study confirm the previously reported findings of the acceptable accuracy of the stick test in the detection of urinary leukocytes [1][2][3]. In addi tion, we also found that technologist bias is lesser when presence of WBCs is evaluated by the dipstick method as compared to sediment analysis.…”
supporting
confidence: 88%
“…Most laboratories rely on microscopic examination of the urine sediment. Recent studies have shown that a chemi cal dipstick test is accurate for detecting significant num bers of white cells in urine [1][2][3]. The purpose of the present study was to evaluate the degree of accuracy with which the stick test predicted the leukocyte concentration in urine as assessed by microscopic analysis of urine sediment.…”
mentioning
confidence: 95%
“…Studies have demonstrated VOL. 1,1988 a correlation between leukocyte esterase activity and the chamber count (43,71 …”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Values for sensitivity, specificity and predictive values show large variations for the different studies (table 6 a, b, c). Originally dipsticks with a leukocyte field requiring 15 minutes reaction time were used (2,5,6,7,8), whereas in later studies more sensitive methods (6), requiring 1-2 minutes reaction time were used (6, 12, 13, 14, 18, 21-25). …”
Section: Discussionmentioning
confidence: 99%
“…In others, special care was taken, such s the use of sterilized Containers and collection of clean voided, midstream or catheter urine (5,7,12,13,14,22).…”
Section: Discussionmentioning
confidence: 99%